Molecular Docking Study of Eugenol and Its Derivatives as Potential Anti-Ischemia Agents for Angiotensin Converting Enzyme (ACE) Inhibition - Prabawati, Susy Yunita; Triatmaja, Karisma; Widiakongko, Priyagung Dhemi (Universitas Gadjah Mada, 2025)
Mortality due to ischemic stroke has increased significantly, especially during the COVID-19 pandemic. Preventive measures are urgently needed to reduce the severity of ischemic stroke, which is mainly caused by blood vessel blockage due to increased secretion of angiotensin II (ANG II) by angiotensin-converting enzyme (ACE). This study investigated the potential of eugenol and its derivatives as ACE inhibitors using molecular docking, an in silico approach for drug discovery by using PLANTS software. The results showed that several eugenol derivatives, including (E)-1-(2-(4-allylphenoxy)acetyl)-4-cinnamoylthiosemicarbazide, exhibited potent ACE inhibition, with docking scores comparable to the native ligand (lisinopril) and superior to several commercial drugs. Physicochemical evaluation revealed that derivatives such as 5a, 5b, 7, and 9a had favorable molecular weight, total polar surface area, and lipophilicity (log P), thereby enhancing their permeability and bioavailability. Drug-likeness analysis confirmed that the compound meets several criteria, including Lipinski, Pfizer, and Golden Triangle rules, highlighting its potential safety and efficacy. Key binding interactions, including hydrogen bonds, hydrophobic interactions, and electrostatic interactions in the ACE active site, further support its candidacy as an ACE inhibitor. These findings suggest that eugenol derivatives are promising candidates for the development of therapies targeting ischemic stroke through ACE inhibition.